Crisscross heart—Morphology, clinical diagnosis, and management options. Issue 1 (14th November 2016) - Gajjar, Trushar; Rao, Jinaga Nageswar; Desai, Neelam
Abstract: Crisscross heart is a rare cardiac malformation characterized by crossing of the inflow streams of the two ventricles due to a twisting of the heart about its long axis. The developmental mechanisms and causes of crisscross heart remain unknown. Neonates present with cyanosis and a systolic murmur. In this study, we report a case of crisscross heart with situs inversus, concordant atrioventricular and ventriculo arterial connection with ventricular septal defect and pulmonary stenosis, and review the literature on this rare cardiac malformation.